Histoplasma capsulatum (Dimorphic Fungus) in India: Biological Features, Virulence Mechanisms, and Clinical Implications of Histoplasmosis. - Atul Khajuria; Ashish Kumar 2; Pradeep Singh 3 (International Journal of Fungi, 2026)
Histoplasmosis is a systemic mycosis caused by the thermally dimorphic fungus Histoplasma capsulatum. Infection is acquired primarily by inhalation of infectious microconidia and may range from asymptomatic infection to severe disseminated disease. Although histoplasmosis has classically been associated with the river valleys of the Americas, it is being increasingly recognized in Asia, including India, where it frequently mimics tuberculosis, leishmaniasis, lymphoma, and leprosy, resulting in delayed diagnosis and treatment. Cutaneous and mucocutaneous manifestations are of particular importance because they may provide the earliest visible clue to systemic infection in both immunocompetent and immunocompromised patients. In India, histoplasmosis was previously considered to be limited mainly to the Gangetic belt. However, recent reports from Himachal Pradesh, Kerala, and other non-Gangetic regions suggest a wider ecological distribution and an increasing clinical burden. Adrenal involvement, progressive disseminated histoplasmosis, and mucocutaneous disease have been reported prominently in Indian cohorts, especially among people living with HIV, transplant recipients, and patients receiving corticosteroids or other immunosuppressive therapy. This review summarizes the current understanding of the biology, virulence mechanisms, epidemiology, clinical manifestations, laboratory diagnosis, and management of H. capsulatum, with special emphasis on Indian data.
Keywords: Histoplasma capsulatum; Histoplasmosis; India epidemiology; Keywords: Cutaneous manifestations; Mucocutaneous lesions; Progressive disseminated histoplasmosis; Thermal dimorphism